Evaluation of safety and tolerability of antiretroviral therapy in pregnant and non-pregnant women - Tyagi, Kamini; Gupta, Veena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The study was conducted to evaluate safety and tolerability of different components of combined antiretroviral therapy (CART) in pregnant and non-pregnant women and to find out substitute of the drug causing intolerance. Methods: An observational study on 75 pregnant and 125 non pregnant, HIV infected women receiving CART, over a period of 1 year (Jan 2013-Jan 20140 in SRN Hospital affiliated to MLN Medical college, Allahabad. All women were examined clinically and investigated for baseline hematology, LFT, RFT, S. Cholesterol levels and blood sugar levels. Safety and tolerability of CART was assessed by clinical assessment, investigations done at 6 months interval or earlier if required. Results: 64% (48) pregnant women and 60.4% (63) non pregnant women had Adverse Effects (AE). Most common AE was Liver Function Abnormality (LFA). Among NRTIs, zidovudine was substituted in 42% (21) pregnant and 17.4% (11) non pregnant women and among NNRTIs, efavirenz was substituted in 92.3% (12) pregnant women and 52.6% (30) non pregnant women. Conclusions: The safety and tolerability of CART in pregnant and non-pregnant women did not differ by class of ARV, but there were differences among individual drugs. Zidovudine, efavirenz and nevirapine were substituted more commonly in pregnant women.